Erastin Reverses ABCB1-Mediated Docetaxel Resistance in Ovarian Cancer - Zhou, Hai-Hong; Chen, Xu; Cai, Lu-Ya; Nan, Xing-Wei; Chen, Jia-Hua; Chen, Xiu-Xiu; Yang, Yang; Xing, Zi-Hao; Wei, Meng-Ning; Li, Yao; Wang, Sheng-Te; Liu, Kun; et al. (Frontiers in Oncology, 2019)
Overexpression of drug efflux transport ABCB1 is one of the main reasons for multidrug resistance (MDR) in cancer cells. Upregulation of ABCB1 accounts for the resistant recurrence to docetaxel therapy in ovarian cancer with poor survival. Erastin is a novel specific small-molecule targeting SLC7A11 to induce ferroptosis. In the present study, we explored the effect of erastin on docetaxel efficacy in ovarian cancer. We demonstrated that the combination of erastin with docetaxel synergistically decreased cell viability, promoted cell apoptosis and induced cell cycle to arrest at G2/M in ovarin cancer cells with ABCB1 overexpressing. Mechanistically, erastin potently blocked the drug-efflux activity of ABCB1 to increase the intracellular accumulation of ABCB1-substrate agents without alteration of the expression of ABCB1. Consequently, erastin can reverse ABCB1-mediated docetaxel resistance in ovarian cancer, indicating that the combination of erastin and docetaxel may offer a potential effective administration for chemo-resistant patients with ovarian cancers.